Impact of ictal subtraction SPECT and PET in presurgical evaluation. (10th November 2020) - Peedicail, Joseph Samuel; Singh, Shaily; Molnar, Christine P.; Numerow, Leonard M.; Gnanakumar, Ruban; Josephson, Colin B.; Scott, James; Federico, Paolo; Wiebe, Samuel; Pillay, Neelan; ,
Abstract: Objective: To assess the relative contribution of ictal subtraction single‐photon emission computed tomography (ISSPECT) and 18 F‐fluorodeoxyglucose positron emission tomography computed tomography (PET) in epilepsy surgery decision making. Materials and methods: A retrospective 3‐year study of consecutive patients with resistant focal epilepsy who underwent ISSPECT and PET to evaluate to what extent these modalities influence decisions in epilepsy surgery and outcomes. ISSPECT imaging was performed in 106 patients and 58 (55%) had PET also. The clinical consensus (ClinC) was the final arbiter for decisions. Post‐surgical outcomes were collected from follow‐up clinics. Non‐parametric statistics were used to assess association and logistic regression to evaluate prediction of outcomes. Results: Of 106 patients, 60 were males (57%). MRI was non‐lesional in 46 (43%). Concordance with ClinC was seen in 80 patients (76%) for ISSPECT, in 46 patients (79%) for PET, and in 37 patients (64%) for ISSPECT + PET. Fifty‐six patients (53%) were planned for intracranial video‐electroencephalography monitoring (IVEM). Those with ClinC‐PET concordance were likely to proceed to IVEM ( p  = 0.02). ClinC‐PET concordance and ClinC‐ISSPECT concordance did not predict decision to proceed to surgery, but VEM‐MRI concordance did in lesional cases ( p  = 0.018). Forty‐five (42%) underwent surgery of which 29 had minimum follow‐up for 1 year (mean, 20 months; SD, 8) and 22 (76%) had Engel class I outcomes. ClinC‐ISSPECT concordance ( p  = 0.024) and VEM‐MRI concordance ( p  = 0.016) predicted Engel class I outcomes. Conclusion: Those with ClinC‐PET concordance were more likely to proceed with IVEM. ClinC‐ISSPECT concordance and VEM‐MRI concordance predicted good surgical outcomes.